2005
DOI: 10.1177/000313480507100116
|View full text |Cite
|
Sign up to set email alerts
|

TFC (Thoracic Fluid Content): A New Parameter for Assessment of Changes in Chest Fluid Volume

Abstract: Clinical assessment of cardiac status can be difficult and incomplete without an assessment of fluid volume status, especially of the lungs. Now, a new parameter is available, thoracic fluid content (TFC). It is an indicator of total fluid volume, both intracellular and extracellular. Because it is measured noninvasively using impedance cardiography (ICG), it could be a welcome addition to the physician's assessment. An evaluation of TFC was performed beginning with 1) an examination of chest impedance (Z) as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…The ability of the noninvasive impedance technique to correctly assess CI and lung water has been demonstrated by many investigators. [10][11][12][19][20][21] ICG is used by more than 8,000 physicians nationwide, primarily in the office setting. Although not specifically tested in prospective fashion, our findings suggest that the noninvasive technique of ICG as a monitor of CI and TFC soon after the trauma patient is brought to the emergency room could be very helpful in management and resuscitation.…”
Section: Discussionmentioning
confidence: 99%
“…The ability of the noninvasive impedance technique to correctly assess CI and lung water has been demonstrated by many investigators. [10][11][12][19][20][21] ICG is used by more than 8,000 physicians nationwide, primarily in the office setting. Although not specifically tested in prospective fashion, our findings suggest that the noninvasive technique of ICG as a monitor of CI and TFC soon after the trauma patient is brought to the emergency room could be very helpful in management and resuscitation.…”
Section: Discussionmentioning
confidence: 99%
“…TFC is an ICG derived measure providing information on the fluid content in the thorax. It was demonstrated that TFC is a reliable parameter for evaluating the hemodialysis and diuretics induced changes in preload (Zalewski et al 2013, Sanidas et al 2009, Graziani et al 2008, van De Water et al 2005, Peacock et al 2000. As a limitation of this measure, the changes in diaphragm position may also cause changes to electrical pathways of transthoracic sensing currents (Zhang et al 2016) introducing a potential error to TFC as a measure of preload in our study during HUT.…”
Section: Study Limitationsmentioning
confidence: 99%
“…Measurement of thoracic fluid content (TFC) using Bioimpedence is based on the theory that the thoracic cavity is an inhomogeneous electrical conductor (19). TFC is derived from the thoracic electrical base impedance (1/base impedance), which is dependent on thoracic intravascular and extravascular fluid content.…”
Section: Introductionmentioning
confidence: 99%
“…Larger TFC indicates a higher total thoracic fluid volume ( 20 ). Potential changes in TFC are directly proportional to total fluid changes ( 21 ). TFC measurement has been correlated with heart failure symptoms, net fluid balance, and chest radiographic findings of abnormal pulmonary fluid content in adults ( 22 ).…”
Section: Introductionmentioning
confidence: 99%